Reading for understanding : Toward an R&D program in reading comprehension - Catherine Snow (Reading Study Group RAND, 2002)
One of the most vexing problems facing middle and secondary school teachers today is that many students come into their classrooms without the requisite knowledge, skills, or disposition to read and comprehend the materials placed before them. In an effort to inform the U.S. Department of Education’s Office of Educational Research and Improvement (OERI) on ways to improve the quality and relevance of education research and development, RAND convened 14 experts with a wide range of disciplinary and methodological perspectives in the field of reading. The RAND Reading Study Group (RRSG) was charged with proposing strategic guidelines for a long-term research and development program supporting the improvement of reading comprehension. This report is the product of that group’s efforts and of the valuable commentary provided by various members of the reading research and practice communities. This report should be of interest to those involved with the planning of education research and development (R&D) programs by public and private agencies, and it should also be of interest to researchers who study reading instruction and practitioners who teach reading. This report is the first in a series of three RAND reports dealing with the topic of education R&D. The second report, scheduled for draft publication in summer 2002, will propose an R&D program for mathematics education and the third report, scheduled for draft publication in fall 2002, will address R&D management issues.